Basket Case! - Wallace, Carden C. (Queensland Review, 2021)
Queensland has some 400 public museums and art galleries. Large or small, these are all dedicated to caring for their part of what is often called the ‘distributed national collection’ and to permanently documenting a segment of our history — social, natural or otherwise. Each of us who steps inside such an institution to help in this effort is liable to become lost to this world for the rest of our working life. We are all, in some sense, collectors, and we tend to be very loyal to ‘our’ subject matter.